COMPARISON IN ESTIMATING RESERVOIR LIFETIME BY UNIVERSAL SOIL LOSS EQUATION AND SITE OBSERVATION (GEOMATE Journal, 2022)
Sedimentation can severely limit the service lifetime and functionality of reservoirs. The application of the Universal Soil Loss Equation (USLE) requires validation of its accuracy and applicability despite its prevalence. This study compares reservoir lifetime predictions for the Leuwikeris Reservoir on the Citanduy River using the USLE model and the suspended load records from the field measurement. The comparison shows a reasonable similarity between the theoretical calculation and the factual observations in determining the amount of watershed soil loss and the reservoir lifetime. Although the validation is successful, USLE and the measurement technique have their specific limitations. In particular, the inability of USLE to consider both gully erosion together with sedimentation and the inability of the measurement technique in detecting bed load. Despite the limitations, these results are in line with previous studies which stated that the USLE model is generally feasible in estimating the quantity of reservoir-bound sediment.